Corporate share repurchases and the 2023 excise tax - Autore, Don M.; Barnes, Spencer; Clarke, Nicholas; Schrowang, Andrew (Journal of Corporate Finance, 2025)
The Inflation Reduction Act of 2022 imposes a 1 % excise tax on US corporate share repurchases, effective January 1, 2023. The tax's implementation is associated with a significant decline in corporate repurchases that is not offset by a corresponding increase in dividends. Aggregate repurchases decline from about $1 trillion in 2022 to just over $800 billion in 2023, and the average firm reduces quarterly repurchases (as a fraction of market capitalization) by roughly 25 %. The decline in repurchases by US firms far exceeds a contemporaneous decline in repurchases by Canadian firms, is large in a historical context, and is not driven by firm fundamentals. Tax-induced cuts to repurchases are associated with an increase in cash but no increase in investment, implying that the tax has not generated the stated policy objective.